2021
DOI: 10.35566/jbds/v1n1/p5
|View full text |Cite
|
Sign up to set email alerts
|

Factor or Network Model? Predictions From Neural Networks

Abstract: The nature of associations between variables is important for constructing theory about psychological phenomena. In the last decade, this topic has received renewed interest with the introduction of psychometric network models. In psychology, network models are often contrasted with latent variable (e.g., factor) models. Recent research has shown that differences between the two tend to be more substantive than statistical. One recently developed algorithm called the Loadings Comparison Test (LCT) was develope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Network loadings of .15, .25, and .35 are equivalent to low (.40), moderate (.55), and high (.70) network loadings, respectively (Christensen & Golino, 2021c ). The development of network loadings opened new lines of research, such as the development of metric invariance using EGA and permutation tests in a network perspective (Jamison et al, 2022 ), and determining whether data are generated from a factor or network model (Christensen & Golino, 2021b ).…”
Section: Methodsmentioning
confidence: 99%
“…Network loadings of .15, .25, and .35 are equivalent to low (.40), moderate (.55), and high (.70) network loadings, respectively (Christensen & Golino, 2021c ). The development of network loadings opened new lines of research, such as the development of metric invariance using EGA and permutation tests in a network perspective (Jamison et al, 2022 ), and determining whether data are generated from a factor or network model (Christensen & Golino, 2021b ).…”
Section: Methodsmentioning
confidence: 99%
“…Woodbury matrix identity [Woodbury, 1950] that oblique factors are statistically consistent with clusters of nodes (i.e., sets of connected nodes) and orthogonal factors are statistically consistent with unconnected clusters in GGM, when the data generation mechanism is a factor model. Christensen and Golino [2021] showed that factor loadings are statistically consistent with a modified version of node strengths (i.e., sum of all connections to a node) that takes into consideration of the dimensionality structure, represented as network loadings.…”
Section: Introductionmentioning
confidence: 67%
“…They showed a simulation study that network loadings are akin to factor loadings, opening a new line of research within the EGA approach. These loadings have opened to door to assessing measurement (metric) invariance (Jamison et al, 2022) from the network perspective as well as determining whether data are generated from a factor or network model (Christensen & Golino, 2021b).…”
Section: Other Developments and Future Directionsmentioning
confidence: 99%